If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4w=6w+11
We move all terms to the left:
4w-(6w+11)=0
We get rid of parentheses
4w-6w-11=0
We add all the numbers together, and all the variables
-2w-11=0
We move all terms containing w to the left, all other terms to the right
-2w=11
w=11/-2
w=-5+1/2
| 12(2.5)=2x2-3x+7 | | 12(2.5)=2x2−3x+7 | | (3x+8)=(7x+4) | | -2-(3+x)=5 | | 3y-1=2y | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x+12 | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x+6 | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x+ | | 2576=23(p+35) | | 2x^2+(4x-6x^2)+9-(6x+3)=-4x^2-2x-6 | | (3x+29)+(6x+7)=180 | | 12c^2-36c=0 | | 2576=23(p+23) | | 4a+12a=0 | | 15-10y=4y-16 | | -5(1-w)=10 | | 7m-12=30 | | 2-4n=7n+3. | | 3x+11x/3=100 | | 6+4m=-10 | | 4x2−4x−3=0 | | 0.5y-y=-9 | | 1/3a+1/2=10 | | 15/x+2=5 | | 4(x+3)-10=10 | | n^+6n+5=8 | | F(2.5)=2x2-3x+7 | | 46.2=46.2p | | e÷4=25 | | 11^-8x=7 | | 3=1/2q+3 | | Y=60+24x |